Schenker's interpretive practice - Snarrenberg, Robert (Cambridge Cambridge University Press, 1997)
Schenkers Interpretive Practice is the first comprehensive study of this centurys most influential music theorist, Heinrich Schenker. Since the 1960s, American theorists and musicologists have focused almost exclusively on analytical methods distilled from Schenkers writings. Breaking from that tradition, Robert Snarrenberg returns to Schenkers texts and to the humanist roots of his approach, situating Schenkers work in the broader context of his